A one dimensional heat transfer model for wolverine (gulo-gulo) hair. Issue 4 (19th July 2018) - Liu, HongYan; Bahi, Addie; Ko, Frank K.
Abstract : Purpose: Wolverine hairs with superior heat transfer properties have been used as fur ruffs for extreme cold-weather clothing. In order to understand the exclusive mechanism of wolverine surviving in the cold areas of circumpolar, the purpose of this paper is to establish a one-dimensional fractional heat transfer equation to reveal the hidden mechanism for the hairs, and also calculate the fractal dimension of the wolverine hair using the box counting method to verify the proposed theory. The observed results (from the proposed model) found to be in good agreement with the box counting method. This model can explain the phenomenon which offers the theoretical foundation for the design of extreme cold weather clothing. Design/methodology/approach: The authors calculated the fractal dimension of the wolverine hair using the box counting method to verify the proposed theory. The observed results (from the proposed model) found to be in good agreement with the box counting method. Findings: The box counting method proves that the theoretical model is applicable. Originality/value: The authors propose the first heat transfer model for the wolverine hair.